2021
DOI: 10.1519/jsc.0000000000003223
|View full text |Cite
|
Sign up to set email alerts
|

AlterG Anti-Gravity Treadmill Accuracy of Unloading Is Affected by Support Frame Height

Abstract: de Heer, HD, Kaufman, A, Repka, CP, Rojas, K, Charley, B, and Bounds, R. AlterG Anti-Gravity Treadmill accuracy of unloading is affected by support frame height. J Strength Cond Res 35(10): 2910–2914, 2021—The AlterG Anti-Gravity Treadmill uses air pressure to provide partial body-weight support (BWS), lowering impact forces and metabolic demand of walking and running. Users wear specialized shorts that zip onto a bag supported by a metal bar frame covering the treadmill. The frame is placed at hip height in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Vertical adjustment of the frame height allows participants of different heights to use the machine. 4 Moreover, a more sensitive adjustment of the body weight support can be provided. Antigravity treadmills allow for support up to 80% of body weight.…”
Section: Support Mechanism Of the Antigravity Treadmillmentioning
confidence: 99%
See 2 more Smart Citations
“…Vertical adjustment of the frame height allows participants of different heights to use the machine. 4 Moreover, a more sensitive adjustment of the body weight support can be provided. Antigravity treadmills allow for support up to 80% of body weight.…”
Section: Support Mechanism Of the Antigravity Treadmillmentioning
confidence: 99%
“…The standard operating instructions of the treadmill states the frame should position the zipper at the iliac crest line, with the caveat that the frame can be adjusted up or down on the basis of the individual preference for more or less trunk stabilization. de Heer et al 4 examined the accuracy of the AlterG unweighting across a range of body weight support levels (from 0% to 60%). Following the standard instructions, the authors found that the greatest accuracy occurred in the 10%-40% BWS range.…”
Section: Technical Considerations For Accurate Unloadingmentioning
confidence: 99%
See 1 more Smart Citation